Territorialização e cultura da violência nos rincões Goianos: as representações do crime no jornal Estado de Goyaz (1891-1896) - Barros, Andreia Pereira (2024)
The present work analyze as representations about criminality in the press of Goiás, at the end of the 19th century and beginning of the 20th century, based on the Jornal o Estado de Goiaz: Orgam do Partido Republicano. The objective is to understand the culture of violence in Goiás, starting from how criminality was defined as crime in the news, in which locality what was defined as crime in the news, highlighting the Boa Vista episode, which is much commented on in the newspaper. To achieve these objectives, a bibliographical discussion was carried out, focusing on an interdisciplinary hermeneutic analysis and mobilizing concepts to direct the research. In addition to identifying the places with the highest crime rate, we sought to map the profile of the social actors who are carried out in crime reports. Parts than all places where most places and the physical force of the supply would not be more evident as “territories or violence of the Saints”, as Thousand places would say the culture of violence were more places and the physical force of Promoting the domestication of the bodies, as Foucault would say (2014) and maintain the public safety.